2004
DOI: 10.1111/j.1524-4725.2004.30105.x
|View full text |Cite
|
Sign up to set email alerts
|

Sebaceous Hyperplasia Treated With a 1450-nm Diode Laser

Abstract: The 1450-nm diode laser is effective and safe for the treatment of sebaceous hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Other procedures that have also been used include excision, electrocauterization, cryotherapy, shaving, curettage and cauterization with chemical agents used topically, although there is a risk of depigmentation or scarring with these latter options. [16][17][18][19][20][21][22][23][24][25] Many laboratory studies have shown the effect of androgens on the sebaceous glands. A review of the literature on several research models confirmed the effect of androgens in triggering the activity of the sebaceous glands and indicated which of these hormones may be implicated in triggering these glands.…”
Section: Introductionmentioning
confidence: 99%
“…Other procedures that have also been used include excision, electrocauterization, cryotherapy, shaving, curettage and cauterization with chemical agents used topically, although there is a risk of depigmentation or scarring with these latter options. [16][17][18][19][20][21][22][23][24][25] Many laboratory studies have shown the effect of androgens on the sebaceous glands. A review of the literature on several research models confirmed the effect of androgens in triggering the activity of the sebaceous glands and indicated which of these hormones may be implicated in triggering these glands.…”
Section: Introductionmentioning
confidence: 99%
“…27 The laser focuses on the water in the skin, which is likely why the upper dermis is heated and therapeutically damaged. 28 Interestingly, the 1450-nm laser appears to induce a systemic effect on the skin, as treatment on only one side of the face in one 2011 study resolved acne lesions on both sides of the face. 29 Unfortunately, in our experience, subsurfacing laser technology has had limited improvement of facial wrinkling.…”
Section: -Nm Diode Laser (Candela Smoothbeam)mentioning
confidence: 99%
“…The laser spot diameter was 6 mm. Three clinically relevant MCS-LPS patterns [5][6][7][19][20][21][22] were applied on the skin specimens. As illustrated in Figure 2, MCS-LPS-1 involved the longest total cryogen spray time (t CSC 1 ¼ 38 milliseconds).…”
Section: Laser Devicementioning
confidence: 99%
“…A diode laser with a wavelength of 1,450 nm in combination with CSC is clinically used for treatment of acne, acne scarring, and non-ablative photorejuvenation [5][6][7]. The laser light is used to target the dermal sebaceous glands and associated structures, while CSC protects the epidermis.…”
Section: Introductionmentioning
confidence: 99%